A novel pollution pattern: Highly chlorinated biphenyls retained in Black-crowned night heron (Nycticorax nycticorax) and Whiskered tern (Chlidonias hybrida) from the Yangtze River Delta. (May 2016) - Zhou, Yihui; Yin, Ge; Asplund, Lillemor; Qiu, Yanling; Bignert, Anders; Zhu, Zhiliang; Zhao, Jianfu; Bergman, Åke
Abstract: Contamination of organochlorine pesticides (OCPs), polychlorinated diphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), hydroxylated polybrominated diphenyl ethers (OH-PBDEs) and their methylated counterparts (MeO-PBDEs) were determined in Black-crowned night heron (Nycticorax nycticorax) and Whiskered tern (Chlidonias hybrida) from two drinking water sources, e.g. Tianmu lake and East Tai lake in Yangtze River Delta, China. A novel PCBs contamination pattern was detected, including 11% and 6.9% highly chlorinated biphenyls (PCBs with eight to ten chlorines) in relation to total PCB concentrations in the Black-crowned night heron and Whiskered tern eggs, respectively. The predominating OCPs detected in the present study were 4, 4′-DDE, with concentration range 280–650 ng g −1 lw in Black-crowned night heron and 240–480 ng g −1 lw in Whiskered tern, followed by β-HCH and Mirex. 6-MeO-BDE-90 and 6-MeO-BDE-99 are the two predominant congeners of MeO-PBDEs whereas 6-OH-BDE-47 contributes mostly to the OH-PBDEs in both species. Contamination level was considered as median or low level compared global data. Graphical abstract: Highlights: A number of POPs were determined in two water bird eggs from Yangtze River Delta. Highly chlorinated biphenyls (CB194-209) were detected in all individual eggs. 4, 4′-DDE was the predominant pesticide in all samples, followed by β-HCH and Mirex. The exposure level of POPs was in the median or low level in the world.